CONFIRMATORY ANALYSIS OF SERVANT LEADERSHIP DIMENSION TO THE INDONESIAN ACADEMIC LEADER - Melinda, Tina; Antonio, Tony; Christina, Christina (Jurnal Aplikasi Manajemen, 2020)
Understanding Leadership in tertiary education is interesting. Greenleaf, the father of Servant Leadership, has been inspired by several Servant Leadership issues in college before he published his seminal paper on servant leadership. After surveying 11 models and scales of Servant leadership we finally apply the 35-item, six-dimension mea- sure of Servant Leadership Behavior Scale (SLBS). This multi-dimensional measurement was developed by Sendjaya. This study investigates and validates the 6 dimensions and 35 attributes of Servant Leadership. A 35-question questionnaire is used to measure the quality of department heads as the academic leaders in higher education. We study the Servant Leadership Dimension of Head of Department with 120 faculty members. Confirmatory factor analysis is performed to verify and validate the dimension of Servant leadership. It is found that the scale can be used in the context of higher education with one or two significant attributes in every dimension.